IMPACT OF COVID-19 ON THE OVERALL SECTOR OF BANGLADESH ECONOMY: AN OVERVIEW - Akter, Marina (Bangladesh Journal of Multidisciplinary Scientific Research, 2021)
After being affected by the Covid-19, Bangladesh also faces challenges related to this pandemic like other countries globally. The impact was spreading to all sectors of the economy. The principal purpose of this study is to give an overview of the pandemic’s impact on the economy as a whole and summarize recommendations for mitigating the pandemic’s devastating effects. This study employs descriptive and exploratory techniques based on secondary data collected from journals, newspapers, published articles, websites, and the internet. The discussion result reveals that, more or less, all the sectors of the economy are affected by the Covid-19 pandemic, not only public health. The study found that Manufacturing industries face losses, and workers are also affected by the various uncertainties about their earnings and job security. The country’s education industry has been hit hard. In a new typical circumstance, students are unsure about studying and are concerned about the academic delay. The Covid-19 pandemic has had an impact on the mental health of students as well as the general public. The study recommends that the government’s intervention, in conjunction with the engagement of relevant sectoral stakeholders, has the potential to recoup losses and design a new strategy or solution to address the problem. JEL Classification Codes: E71, A31, F6, I1.